EMÍLIA FREITAS E A ESCRITA DE AUTORIA FEMININA NO SÉCULO XIX - Silva, Régia Agostinho da (Outros Tempos: Pesquisa em Foco - História, 2010)
This paper focuses on the role of Emilia Freitas, (1855-1908), in the nineteenth century as a writer and abolitionist spirit. To that end we take the book "The Queen of Ignoto" published by the author in 1899 to understand the narrative from that singular action of Emilia Freitas lyrics in the world of nineteenth-century, a period when we were rare and books written by women, as in which writing authored by women, although little can also help us understand the female world of the nineteenth century and the society around him.